ARTIFICIAL INTELLIGENCE (AI) IN EDUCATION: INTEGRATION OF AI INTO SCIENCE EDUCATION CURRICULUM IN NIGERIAN UNIVERSITIES - T.G. Olatunde- Aiyedun (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This study investigates the integration of artificial intelligence (AI) into science curricula at Nigerian universities, motivated by the imperative to prepare students for the evolving demands of the digital age. Employing a mixed-methods approach, the research explores the impact of AI integration on learning outcomes, student engagement, and overall educational quality in science education. Quantitative analysis focuses on academic records, assessing the performance metrics of 180 science education students enrolled in AI-integrated courses across three Nigerian universities. Diverse representation across institutions and academic levels ensures comprehensive insights. Qualitative data, gathered through semi-structured interviews with three experienced lecturers, delves into their perspectives on AI integration in science education. Interviews, conducted via online platforms, highlight the rationale for integrating AI into the curriculum and the lecturers' experiences with AI in their classrooms. Statistical analysis of quantitative data, including regression analysis, identifies patterns and correlations in student performance. Qualitative data undergoes thematic analysis, revealing key insights and recurring themes within educators' and students' narratives. The results demonstrate a tangible link between AI integration and science education, offering a nuanced understanding of advantages and disadvantages. This research advocates for an adaptive curriculum that equips students with AI-related skills, contributing valuable insights for educational stakeholders on effective AI integration into science curricula. Ultimately, the study aims to foster the development of future experts capable of leveraging AI for scientific innovation in Nigeria's evolving technological landscape.